Conceptual Study of Consumers’ Intention to Purchase Sustainable Building in Malaysia - Siew Lim, Woon; Mohd Suki, Norazah (International Journal of Psychosocial Rehabilitation, 2020)
Adherence to the strict compliance set by authority regulations for sustainable building projects is deemed necessary among the building developer firms towards gaining a competitive advantage. This conceptual paper aimed to study what determines consumers’ intention to purchase sustainable buildings is minimal, especially in a developing country. Thus, the goals of this study are fivefold: (i) to investigate the influence of attitude, subjective norm, perceived behavioral control, environmental concern, environmental knowledge, and government incentive on consumers’ intentions to purchase sustainable building in Malaysia, (ii) to examine the influence of environmental concern on consumers’ attitude towards purchasing sustainable building, (iii) to assess the influence of environmental concern on subjective norm towards purchasing sustainable building, (iv) to inspect the influence of environmental knowledge on subjective norm towards purchasing sustainable building, and (v) to test the influence of government incentive on perceived behavioral control towards purchasing sustainable building. This research applies the extended theory of planned behavior (TPB) as a study guiding principle. The research finding said the building developer firms should examine the most significant predictor of consumers’ intentions to purchase sustainable buildings in Malaysia. Besides, with this research offers important insight to the building developer firms towards meeting consumers’ challenging needs and wants